Buckling and crush resistance of high-density TRIP-steel and TRIP-matrix composite honeycombs to out-of-plane compressive load. (1st August 2015) - Ehinger, D.; Krüger, L.; Martin, U.; Weigelt, C.; Aneziris, C.G.
Highlights: Novel zirconia particulate steel composite honeycombs with TRIP effect. Significant difference from past studies on compressive behavior of honeycombs. Deformation behavior controlled by local, torsional and global buckling modes. Strain rate anomaly of the crush resistance due to damage and sample heating. Initial mechanical responses of the honeycombs and the bulk specimens are similar. Abstract: The mechanical and structural responses of high-density TRIP steel and TRIP-steel/zirconia composite honeycomb structures were studied under uniaxial compression in the out-of-plane loading direction over a wide range of strain rates. Their mechanical response, buckling, and failure mechanisms differ considerably from those of conventional thin-walled, low-density cellular structures. Following the linear-elastic regime and the yield limit of the bulk material, the high-density square honeycombs exhibited a uniform increase in compression stress over an extended range of (stable) plastic deformation. This plastic pre-buckling stage with axial crushing of cell walls correlates with the uniaxial compressive response of the bulk specimens tested. The dominating material effects were the pronounced strain hardening of the austenitic steel matrix accompanied by a strain-induced α'-martensite nucleation (TRIP effect) and the strengthening effect due to the zirconia particle reinforcement. The onset of critical plastic bifurcation was initiated at high compressive loads governed by local or global cell wall deflections. After exceeding the compressive peak stress (maximum loading limit), the honeycombs underwent either a continuous post-buckling mode with a folding collapse (lower relative density) or a symmetric extensional collapse mode of the entire frame (high relative density). The densification strain and the post-buckling or plateau stress were determined by the energy efficiency method. Apart from relative density, the crush resistance and deformability of the honeycombs were highly influenced by the microstructure and damage evolution in the cell walls as well as the bulk material's strain-rate sensitivity. A significant increase in strain rate against quasi-static loading resulted in a measured enhancement of deformation temperature associated with material softening. As a consequence, the compressive peak stress and the plastic failure strain at the beginning of post-buckling showed an anomaly with respect to strain rate indicated by minimum values under medium loading-rate conditions. The development of the temperature gradient in the stable pre-buckling stage could be predicted well by a known constitutive model for quasi-adiabatic heating.